2012
DOI: 10.1038/jes.2012.4
|View full text |Cite
|
Sign up to set email alerts
|

Recreational use assessment of water-based activities, using time-lapse construction cameras

Abstract: Recreational exposure to surface waters during periods of increased pathogen concentration may lead to a significantly higher risk of illness. However, estimates of elementary exposure factors necessary to evaluate health risk (i.e., usage distributions and exposure durations) are not available for many non-swimming water-related activities. No prior studies have assessed nonswimming water exposure with respect to factors leading to impaired water quality from increased pathogen concentration, such as weather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…Several other authors have used time-lapse cameras to assess water-based recreational activities (Smallwood et al 2011;Sunger et al 2012). Cuddeback (Expert Model) cameras were installed at each lake on a tree at the shoreline.…”
Section: Appendix Bmentioning
confidence: 99%
“…Several other authors have used time-lapse cameras to assess water-based recreational activities (Smallwood et al 2011;Sunger et al 2012). Cuddeback (Expert Model) cameras were installed at each lake on a tree at the shoreline.…”
Section: Appendix Bmentioning
confidence: 99%
“…Behaviours involving potential contact with sediment/mud in urban areas (e.g. swimming, wading, bathing/washing, fishing, walking barefoot, fishing, picnicking and collecting trash along shorelines) can potentially result in infection and have been documented in or near urban waterways (Donovan, Unice, Roberts, Harris, & Finley, ; Sunger & Haas, ; Sunger, Teske, Nappier, & Haas, ). We also note that the Baermann technique, which is used to diagnose Strongyloides , involves suspending faecal matter in cloth (“coarse fabric”) and analysing larvae that have migrated through that cloth (Siddiqui & Berk, ).…”
Section: Urban Transmission—environmental and Veterinary Connectionsmentioning
confidence: 99%
“…For scenario 2, recreational activities included boating, fishing, and swimming (Table 3). These were selected based on reported frequent water exposure activities as well as suggested designated water uses on the Delaware River [2,40]. The scenario assumed a full day of recreation that included all three activities.…”
Section: Data Sourcesmentioning
confidence: 99%
“…For a worst-case scenario, it was assumed that a full day of recreation occurred once every week for the full recreational season of the year (May-September, 5 months). Exposure duration statistics for fishing and boating were obtained from the study conducted by Sunger and co-authors that specifically observed recreational activities on the Delaware River [40]. However, for swimming, the United States Environmental Protection Agency (EPA) default exposure duration for children less than 6 years of age was considered [41].…”
Section: Data Sourcesmentioning
confidence: 99%